Patriot [compact disc, unabridged] - Bell, Ted (Bell, Ted. Alex Hawke novel, 2015)
In corrupt Russia, an erratic Vladimir Putin is determined to forge his country into a formidable superpower once again. He intends to redraw the map of Europe, and will go to impossible extremes to realize his fantasies; including shooting down a civilian airliner packed with tourists bound for China. Kremlin scientists have developed a radical new weapon that could forever alter modern warfare. NATO locked in a tense standoff over Ukraine, Poland, and Estonia, knows Putin will not hesitate to use it. But there is one man who can bring the world back from the brink: Britain's foremost intelligence asset, Lord Alexander Hawke.